Bronchiolitis Obliterans Organizing Pneumonia as an Initial Presentation of Systemic Lupus Erythematosus: A Rare Case Report and Literature Review - Hung-Ping Wang; Chun-Ming Chen; Yih-Yuan Chen; Wei Chen (Case Reports in Medicine)
The etiology of bronchiolitis obliterans organizing pneumonia (BOOP) remains controversial. While it has been reportedly associated with several connective tissue disorders, there are only rare reports of BOOP associated with systemic lupus erythematosus (SLE). Herein, we report a 56-year-old female patient who presented with dyspnea on exertion, cough, fever, and joint pain of her left wrist and fingers as initial symptoms. Laboratory tests revealed positivity for anti-nuclear antibody, anti-Ro, and anti-double strand DNA antibody. In this case, the patient with SLE had respiratory illness as the initial symptom due to BOOP in the absence of clear etiology. The diagnosis of BOOP was confirmed by thoracic surgery biopsy. Her respiratory symptoms and radiologic findings significantly improved following prednisolone treatment.